ANALYSIS TO DETERMINE WHETHER THERE IS AN EFFECT OF INTEREST IN LEARNING ON GRADE 10 STUDENTS' GRADES IPA 2 - Resnalia Resnalia (Kopertis Region IV Jabar and Banten, 2022)
The purpose of this test is to see whether there is an effect of student learning interest on student grades or learning outcomes, the method used is a survey, this method is used because it is considered that the results written truly reflect student learning abilities, while the sample used is 35 students. . The instrument used was the distribution of questionnaires to see student interest and also questions to see students' abilities, where the results for regression testing for class 10 IPA 2 student interest in learning did not affect the value or student learning outcomes, it was hoped that students would be able and could increase their enthusiasm for learning especially in the eyes of physics studies.